What drives Islamic banks’ credit risk in the long run? a macroeconomic approach - Abduh, Muhamad; Nursechafia, Nursechafia (2013)

(untitled)
Credit risk is the most anticipated risk in the banking system. It is one of the key elements to measure systemic risk and stress testing financial fragility which is very helpful to formulate macro-prudential surveillance in financial systems. Unlike the conventional banking, the empirical evidence of macro-credit risk link in Islamic banking is still considered as an underdeveloped area. Consequently, a further research regarding the stability of the Islamic banking industry has risen to the substantial agenda. Hence, this paper is aimed at determining and assessing the long run vulnerabilities of Islamic financing quality as a response to changes in key macroeconomic variables by using time series econometric approaches of cointegration and vector autoregression (VAR). By simulating variance decomposition (VD) and impulse response function (IRF), it is found that there is evidence of long-run relationship between credit risk ratio in Islamic bank and the selected macroeconomic variables. The exchange rate, supply side-inflation, and growth have negatively driven credit risk rate in Islamic banking, while money supply and Islamic interbank money market rate have positively driven the risk rate.